Association between bone mineral density T-score and respiratory sarcopenia in older adults - Ying Liu; Yutong Guo; Shun Xie; Yunyuan Kong; Jixiong Xu (Frontiers in Medicine)
IntroductionRespiratory sarcopenia, characterized by reduced respiratory muscle mass and strength, is underdiagnosed in older adults. This cross-sectional study aimed to investigate the association between bone mineral density (BMD) T-score and respiratory sarcopenia in a Chinese population.MethodsA total of 530 participants aged ≥60 years were recruited. Respiratory sarcopenia was diagnosed based on peak expiratory flow rate (PEFR) cutoffs. BMD was measured using dual-energy X-ray absorptiometry, and muscle mass was assessed using bioelectrical impedance analysis. Logistic regression models were used to analyze the association between BMD T-score and respiratory sarcopenia risk.ResultsParticipants with respiratory sarcopenia exhibited lower BMD T-score, appendicular skeletal muscle index, trunk muscle mass ratio, and lung function parameters compared to those without respiratory sarcopenia. The odds ratio (95% CI) for the lowest BMD T-score tertile with the risk of respiratory sarcopenia was 4.52 (1.71–13.1) compared with the highest tertile. This association remained significant after adjusting for confounding factors.ConclusionBMD T-score is significantly associated with an increased risk of respiratory sarcopenia in older adults. This finding highlights the importance of bone mass monitoring and early prevention strategies to reduce the incidence of respiratory sarcopenia.